Isospora species (I. canaria, Isospora sp.) in canaries (Serinus canarius, Linnaeus) - Saki, Cem Ecmel; Ozer, Edip (Tubitak Scientific & Technological Research Council Turkey, 2012)
Of 64 canaries with diarrhea in Elazig Province between May 2002 and May 2006, 18 (28.1%) had Isospora oocysts in their feces. It was determined that the oocysts, examined morphologically before and aft er sporulating, were Isospora canaria and Isospora sp. Among the infected animals, 8 (44.4%) were concurrently infected with both species. Total numbers of I. canaria oocysts were greater than those of Isospora sp. A total of 2 canaries showing severe clinical signs were necropsied. Liver, spleen, and lung preparations and peripheral blood smears of the necropsied animals were examined for Atoxoplasma, and no development forms were seen. For this reason it was concluded that the developing forms seen in intestinal tissue preparations belonged to Isospora. Determination of the coccidiosis agents in canaries in Turkey was first revealed with this study.
Keywords: Isospora; canary